A case of isolated primary chylopericardium. Issue 4 (April 1979) - Ross, P; Joseph, S; Walker, D
Abstract : Primary chylopericardium presented as radiographic cardiomegaly in an asymptomatic 19-year-old man. Normal findings at cardiac catheterisation and angiographic demonstration of cardiac displacement from the diaphragm suggested a collection of fluid below the heart which was confirmed by M and B mode ultrasound scanning. Thoracic blood pool isotope scanning indicated that the lumen was a pericardial effusion rather than a cyst. Lymphangiography did not indicate any direct lymphatic communication though a small pool of contrast appeared in the pericardium and the diagnosis of chylopericardium was confirmed by pericardiocentesis. Surgical treatment was undertaken after rapid reaccumulation of chyle and the patient remains well 6 months later.